Biology of Acrosternum marginatum (Heteroptera: Pentatomidae) on common beans - Hallman, GJ; Morales, C.G.; Duque E., Myriam Cristina (1992)
The biology of Acrosternum marginatum (Palisot de Beauvois) (Heteroptera: Pentatomidae) on common bean, Phaseolus vulgaris L., was studied at a mean temperature of 24@*C (range 19-32@*C) near Palmira, Colombia. Total mean (@+SEM) developmental time from egg to adult was 42.1 @+ 4.2 d. Head capsule widths of the five instars did not overlap. The female lived a mean of 44.4 @+ 2.84 d and laid 96.2 @+ 9.72 eggs in 7.5 @+ 0.74 masses. The mean preovipositional period was 10.1 @+ 1.31 d. The time interval between consecutive ovipositions fit the geometric distribution with P (the probability that a female will oviposit on any day) = 0.19 (included first oviposition) or P = 0.22 (excluded first oviposition). The mean number of eggs per mass was 12.8, with a marked peak at 14. There were no significant correlations between the number of days between consecutive ovipositions nor age of female versus number of eggs per mass. Mean emergence from egg masses was 80 @+ 0.77%. Percentage emergence was not significantly related to the number of days since the previous oviposition nor age of the female.